Comparing Inhaled Ultrafine versus Fine Zinc Oxide Particles in Healthy Adults: A Human Inhalation Study - Beckett, William S; Chalupa, David F; Pauly-Brown, Andrea; Speers, Donna M; Stewart, Judith C; Frampton, Mark W; Utell, Mark J; Huang, Li-Shan; Cox, Christopher; Zareba, Wojciech; Oberdorster, Gunter (American journal of respiratory and critical care medicine, 2005)
Zinc oxide is a common, biologically active constituent of particulate air pollution as well as a workplace toxin. Ultrafine particles (< 0.1 microm diameter) are believed to be more potent than an equal mass of inhaled accumulation mode particles (0.1-1.0 microm diameter). We compared exposure-response relationships for respiratory, hematologic, and cardiovascular endpoints between ultrafine and accumulation mode zinc oxide particles. In a human inhalation study, 12 healthy adults inhaled 500 microg/m3 of ultrafine zinc oxide, the same mass of fine zinc oxide, and filtered air while at rest for 2 hours. Preexposure and follow-up studies of symptoms, leukocyte surface markers, hemostasis, and cardiac electrophysiology were conducted to 24 hours post-exposure. Induced sputum was sampled 24 hours after exposure. No differences were detected between any of the three exposure conditions at this level of exposure. Freshly generated zinc oxide in the fine or ultrafine fractions inhaled by healthy subjects at rest at a concentration of 500 microg/m3 for 2 hours is below the threshold for acute systemic effects as detected by these endpoints.